2021
DOI: 10.3390/s21196445
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Hand Vein Image Enhancement Using Fusion of CLAHE and Fuzzy Adaptive Gamma

Abstract: Enhancement of captured hand vein images is essential for a number of purposes, such as accurate biometric identification and ease of medical intravenous access. This paper presents an improved hand vein image enhancement technique based on weighted average fusion of contrast limited adaptive histogram equalization (CLAHE) and fuzzy adaptive gamma (FAG). The proposed technique is applied using three stages. Firstly, grey level intensities with CLAHE are locally applied to image pixels for contrast enhancement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It can be seen the experimental imaging results of the first person in Fig. 4 PSNR is one of the commonly used metric for the evaluation of any enhanced medical images [23][24][25][26], and DSI is one of the widely used another metric for the evaluation of segmented medical images [27][28][29][30], it was calculated as…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen the experimental imaging results of the first person in Fig. 4 PSNR is one of the commonly used metric for the evaluation of any enhanced medical images [23][24][25][26], and DSI is one of the widely used another metric for the evaluation of segmented medical images [27][28][29][30], it was calculated as…”
Section: Resultsmentioning
confidence: 99%
“…In four studies [23][24][25][26], the MSE and PSNR values of the enhancement methods in each step applied to the image were calculated and shown that the method with the highest PSNR value versus the lowest MSE value is the best method. In our study, as seen in Tab.…”
Section: Discussionmentioning
confidence: 99%